2020
DOI: 10.4236/aim.2020.105019
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Diagnosis and Control of Enterotoxaemia Caused by <i>Clostridium perfringens</i> in Small Ruminants

Abstract: Enterotoxaemia is one of the important pathologies caused by Clostridium perfringens, which produces intestinal and systemic disease in goats, sheep and other animals. These Gram-positive anaerobic bacteria are normally resident in the intestinal tract of ruminants but during favourable conditions, proliferate uncontrollably and release toxins which produce disease in the How to cite this paper:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 172 publications
2
4
0
Order By: Relevance
“…The clinical signs observed are in consistent with that of Smith and Sherman (2011) and Ortega et al (2019). Diarrhoea was the most consistent finding which is due to enterocolitis in acute cases and initial softening of faeces in sub acute cases (Pawaiya et al, 2020). The nervous signs observed could be associated with ETX that was known to stimulate the release of glutamate, an excitatory neurotransmitter, by targeting the hippocampal glutamatergic system (Lonchamp et al, 2010 andPopoff, 2011) or vasogenic edema and neuronal toxicity (Morris et al, 2017).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The clinical signs observed are in consistent with that of Smith and Sherman (2011) and Ortega et al (2019). Diarrhoea was the most consistent finding which is due to enterocolitis in acute cases and initial softening of faeces in sub acute cases (Pawaiya et al, 2020). The nervous signs observed could be associated with ETX that was known to stimulate the release of glutamate, an excitatory neurotransmitter, by targeting the hippocampal glutamatergic system (Lonchamp et al, 2010 andPopoff, 2011) or vasogenic edema and neuronal toxicity (Morris et al, 2017).…”
Section: Resultssupporting
confidence: 82%
“…However, in ia (150 to 200 mg/dL) due to the mobilization of hepatic glycogen and marked glycosuria are reported to be characteristic in the terminal stage of enterotoxaemia (Constable et al, 2017). Glycosuria is said to be strongly indicative of enterotoxaemia in both sheep and goats (Uzal and Songer, 2008), where as Pawaiya et al (2020) reported the hyperglycaemia and glycosuria to be inconsistent in goats.…”
Section: Control Positivesmentioning
confidence: 99%
See 1 more Smart Citation
“…When lambs are between four to ten weeks old, they need to be vaccinated with toxoid and then again, one month later. While waiting for vaccination immunity to develop, decreasing food intake is an effective means of shortterm control measure (Pawaiya et al 2020).…”
Section: Treatment Prevention and Controlmentioning
confidence: 99%
“…The majority of enteric infections, often known as enterotoxaemia, in sheep and goats were caused by C.perfringens. This microbe is typically present in the intestinal flora of both humans and animals (Pawaiya et al, 2020), but under exceptional conditions where the physiological balance of the intestine is disturbed, it can proliferate rabidly and cause disorders related to a variety of toxins (Bourlioux et al, 2003).…”
Section: Introductionmentioning
confidence: 99%